Casa Rural - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: construccion de casa rural amazomico con materiales del entorno con techo de hojas de irapay y troncos de madera.
ENGLISH: construction of rural amazomico house with materials of the environment with roof of irapay leaves and wood trunks.

SPANISH: construccion de casa rural amazomico con materiales del entorno con techo de hojas de irapay y troncos de madera.
ENGLISH: construction of rural amazomico house with materials of the environment with roof of irapay leaves and wood trunks.
Rural House
Keywords: Iquitos (Perú)|~|Rural houses|~|Perú|~|Amazonian cottages|~|Perú|~|Rural houses|~|Iquitos (Perú)|~|Casas Rurales|~|Perú|~|Casas rurales amazonicos|~|Perú|~|Casas Rurales|~|Iquitos (Perú)|~|Rural Houses|~|Peru|~|Amazonian cottages|~|Peru|~|Rural Houses